N, P and S co-doped carbon materials derived from polyphosphazene for enhanced selective U(VI) adsorption - Liu, Yan (2021)
Herein, the precursor polyphosphazene was synthesized by the polymerization of hexachlorocyclotriphosphazene (HCCP) and bis(4-hydroxyphenyl) sulfone (BPS). The adsorbent which was codoped with N, P and S (amidate-CS) was developed from the precursor by using the carbonization method. The images of Scanning electron microscope (SEM) and Transmission electron microscope (TEM) indicate that the amidate-CS possessed porous graphene-like carbon lamellar structure. The excellent behaviors with respect to kinetics (120 min for equilibrium) and thermodynamics (maximum removal of 290 mg/g when pH was at 6.0) revealed the outstanding performance of amidate-CS in removing U(VI), which is due to the functional groups and strong covalent bonds between heteroatoms and uranyl ions. The adsorption of amidate-CS followed the pseudo-second-order kinetic and Langmuir adsorption model. The thermodynamic parameters indicate that the process was spontaneous and endothermic. The adsorption and desorption efficiency of amidate-CS had a slight decrease after five cycles, indicating excellent regeneration performance. Overall, the amidate-CS is a prospective candidate for highly selective U(VI) removing.